Analysis of the relationship between the surface topography of prepared tooth surfaces and data quality of digital impressions from an intraoral scanner - Neset Volkan Asar; Sarah Yun; Shelby Schwartz; Ilser Turkyilmaz (Elsevier, 2022)
Background/purpose: With the rise of digitalization in dentistry, intraoral scanners and digital impressions have recently been adopted by many clinicians. The aim of this study was to investigate surface topography of prepared teeth and the accuracy of digital impressions. Materials and methods: Twenty mandibular typodonts, containing left first premolar and left first molar abutment teeth manufactured by using CAD/CAM, were used in this study. An intraoral scanner was used to scan each typodont, and each STL file generated was exported in high resolution (Group H), moderate resolution (Group M), and low resolution (Group L). All 60 files were inspected in a 3-D mesh processing software. For each file, the number of triangulation points in the meshwork were obtained for both abutment teeth. Results: The measurements obtained from the 3-D mesh processing software revealed that the mean number of triangulation points on the 3-D surface of the abutment teeth (20 premolars + 20 M) were 790,625 ± 98,890 dots in Group H, 592,283 ± 74,881 dots in Group M, and 198,067 ± 19,328 dots in Group L. Significant differences were found between Group H and M (p < 0.05), Group H and L (p < 0.001), and Group M and L (p < 0.01). Conclusion: The outcomes of this study reveal that there are strong correlations between the data quality of digital impressions and surface topography of prepared teeth. Therefore, the utilization of STL files in high resolution format is the recommended choice for clinicians engaging in a digital workflow process.